Response to propranolol as a clue to the diagnosis of hemangioma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2013)
Although it is still more difficult to administer propranolol compared to cortisone (1), the former from 2008 (2) is the drug of first choice in the systemic treatment of those hemangiomas who need a therapy. Compared with cortisone, propranolol has equal efficacy but significantly reduced side effects. The most severe side effect of propranolol is hypoglycemia, which occurs in 10% of cases if blood glucose is monitored throughout treatment, but only in exceptional cases (1 case of 150 in our series) takes on clinical significance. The most frequent side effect is the partial rebound of hemangioma (usually not more than 10%) when withdrawing the treatment. Moreover, in our experience propranolol can also be used as a diagnostic criterion in case of deep hemangiomas (retrobulbar, of the glottis) when imaging techniques are not diriment.